2015
DOI: 10.1038/bmt.2015.194
|View full text |Cite
|
Sign up to set email alerts
|

A prospective investigation of cell dose in single-unit umbilical cord blood transplantation for adults with high-risk hematologic malignancies

Abstract: Umbilical cord blood (UCB) as an allogeneic transplant source is generally limited to units with pre-cryopreservation total nucleated cell (TNC) doses ⩾ 2.5 × 10 7 NC/kg. We prospectively investigated single UCB transplantation, with cord units as low as 1 × 10 7 NC/kg, all processed with post-thaw albumin-dextran dilution. We transplanted 104 adult patients with 84% having relapsed/ refractory disease. The median TNC dose was 2.1 × 10 7 NC/kg (range: 1.0-4.4 × 10 7 ) and median CD34+ cell dose was 1.0 × 10 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We previously reported the safety of single-unit CBT for adults with the low cryopreserved TNC dose (less than 2 × 10 7 /kg) [56]. Recently, Sobol et al prospectively evaluated the minimum threshold of cryopreserved TNC dose in single-unit CBT for adults and found that transplantation outcomes in patients receiving the cryopreserved very low TNC dose (1 to 1.5 × 10 7 /kg) was similar to that of the entire cohort [57]. Therefore, future studies are required to investigate the minimum threshold of cryopreserved TNC dose, as well as CD34 + cell or CFU-GM doses, in singleunit CBT for adults.…”
Section: Discussionmentioning
confidence: 96%
“…We previously reported the safety of single-unit CBT for adults with the low cryopreserved TNC dose (less than 2 × 10 7 /kg) [56]. Recently, Sobol et al prospectively evaluated the minimum threshold of cryopreserved TNC dose in single-unit CBT for adults and found that transplantation outcomes in patients receiving the cryopreserved very low TNC dose (1 to 1.5 × 10 7 /kg) was similar to that of the entire cohort [57]. Therefore, future studies are required to investigate the minimum threshold of cryopreserved TNC dose, as well as CD34 + cell or CFU-GM doses, in singleunit CBT for adults.…”
Section: Discussionmentioning
confidence: 96%
“…The probable reason could be too few cases in this subgroup. Taking the results reported by most others and us together, 35–37 these studies indicated that CD34 + stem and progenitor cells in the allografts contributed to haematological reconstitution in patients who received allo‐HSCT, which was not affected by the underlying diseases, conditioning regimen, and stem cell sources, for example, bone marrow harvests, peripheral blood stem cells or mixture allografts of G‐CSF mobilized bone marrow and peripheral blood harvests. Therefore, a myriad of previous research and our study provided evidence suggesting that a sufficient CD34 + cell dose collected from healthy donors was needed to ensure successful haematopoietic recovery 3,6 …”
Section: Discussionmentioning
confidence: 92%
“…18 Influence of ABO mismatched on transfusion requirements in patients who underwent HSCT remains controversial. [22][23][24][25] Major ABO incompatibility has been associated in some studies with increased RBC transfusion burden after bone marrow or peripheral 29 with a higher number of patients with acute leukemia who underwent a haplo-HSCT showed that major ABO incompatibility is associated with inferior engraftment rate at day 100 and bi-directional mismatching was associated with increased risk of grade II-IV GVHD. Unfortunately, they do not provide information about transfusion requirements.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation may be the smaller sample size of the present study. It has been reported that CD34 + cell dose in the cord blood grafts significantly predicts faster neutrophil and platelet engraftment, and therefore it must be considered in the graft selection . A large study including 800 patients who received matched sibling peripheral blood transplantations confirmed that lower CD34 + cell doses are significantly related to slower graft recovery and, therefore, an increase of transfusion needs …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation